TEMPE BUSINESS DEVELOPMENT MODEL BASED ON PENTA HELIX REVIEWED FROM MAQASHID SYARIAH (CASE STUDY OF SEI RAMPAH VILLAGE) - Alfiani, Rani; Nasution, Juliana; Syahbudi, Muhammad (istinbath, 2024)
This research aims to determine and describe the implementation of the pentahelix model in developing MSMEs, especially the tempe business in Sei Rampah Village, using maqashid sharia principles. Pentahelix is ​​​​a series of models that are the result of the development of the model that connects Academics, Business, Community, Government, and Media in developing innovation and the economy. This research method uses a qualitative descriptive method using the pentahelix method. The data collection techniques used in this research are observation, interviews, and literature study techniques. The research results show that the development of the tempe business in Sei Rampah Village has involved the five actors in the pentahelix model: academics, business, community, government, and media. However it is implemented, there are obstacles to its role. This research also concluded that Islamic economics is closely related to maqashid shari'ah, namely hifz al-mal. Maqashid shari'ah is the basis for the development of Islamic economics because it aims to create human welfare and happiness by balancing the circulation of wealth in a fair and balanced manner, personally and socially.